ESTUDO DA CORROSÃO DO AÇO INOXIDÁVEL AUSTENÍTICO TIPO ABNT 304 EM ETANOL DERIVADO DA GLICERINA - Antunes Junior, Osmar dos Reis (2013)
The main byproduct of the biodiesel obtained in the synthesis is glycerol. Employing microorganisms in the decomposition of glycerol, obtains a second-generation biofuel, ethanol. This alcohol can be used as a corrosion inhibitor for ferrous alloys. The objective of this work was to study the electrochemical behavior of 304 stainless steel in H2SO4 2 mol L?¹ in the absence and presence of 0,5%; 1,0; 2,5; 5,0; 7,5; 10 and 20% ethanol v / v. Ethanol was produced by microbiological fermentation of glycerol by Eschericchia coli in culture medium dextrose, peptone, tryptose, lactose. The electrochemical techniques were employed: testing open circuit potential (ECA), electrochemical impedance spectroscopy (EIS), anodic polarization (PPA) and cathode and (PPC) electrical conductivity and optical microscopy (MO). The medium which operated more efficiently as a catalyst in the conversion of glycerol was lactose. The results of the tests demonstrated that ECA corrosion potential (Ecorr) of 304 stainless steel in an acid medium with and without ethanol were averaged 851 ± 2 mV / Hg(l)/Hg2SO4(s). The curves of PPA 304 stainless steel in H2SO4 2 mol L?¹ indicated that when the alcohol concentration increases the rate of oxidation decreases. In these tests two peaks were observed in the active region of the metal at about -0,730 and -0,780 mV / Hg(l)/Hg2SO4(s). in the presence of 1.0%, 2.5%, 7.5% to 20% of ethanol. The curves indicated PPS lower values of current density obtained for samples immersed in medium 1, 5, and 20% ethanol inhibitory effect characterizing a cathode. EIS diagrams presented capacitive two curves both for the system in the absence or presence of ethanol, possibly the arc associated to the first charge transfer and the second adsorption of ethanol on the substrate, suggests a physical adsorption. The electrical conductivity allowed to predict the order of reaction for the oxidation of 304 stainless steel in H2SO4. It was observed stepped surface indicating an inhibition of the ethanol in attack of 304 stainless steel and a corrosion generalized preferably with high corrosion between the grains.